2013
DOI: 10.1371/journal.pone.0069402
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation at the MHCIIα and Cath2 Loci in Sympatric Salvelinus alpinus Resource Morphs in Lake Thingvallavatn

Abstract: Northern freshwater fish may be suitable for the genetic dissection of ecological traits because they invaded new habitats after the last ice age (∼10.000 years ago). Arctic charr (Salvelinus alpinus) colonizing streams and lakes in Iceland gave rise to multiple populations of small benthic morphotypes, often in sympatry with a pelagic morphotype. Earlier studies have revealed significant, but subtle, genetic differentiation between the three most common morphs in Lake Thingvallavatn. We conducted a population… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
39
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 32 publications
(47 citation statements)
references
References 80 publications
6
39
1
Order By: Relevance
“…Importantly Kapralova et al (2011) 51 concluded that small benthic morphs have evolved repeatedly in Iceland and that gene flow has been reduced between the PL and SB morphs in Lake Thingvallavatn since its formation approximately 10,000 years ago 53 . We also discovered genetic separation in immunological genes ( MHCIIα and cath2 ) between morphs in Iceland and within the lake 52 , consistent with ecologically driven evolution of immune functions. Recently qPCR analyses showed that expression of mTOR pathway components in skeletal muscle correlates with the SB-charr form in Iceland 54 , but it is unknown whether there is genetic differentiation in those genes or upstream regulators.…”
Section: Introductionsupporting
confidence: 57%
See 4 more Smart Citations
“…Importantly Kapralova et al (2011) 51 concluded that small benthic morphs have evolved repeatedly in Iceland and that gene flow has been reduced between the PL and SB morphs in Lake Thingvallavatn since its formation approximately 10,000 years ago 53 . We also discovered genetic separation in immunological genes ( MHCIIα and cath2 ) between morphs in Iceland and within the lake 52 , consistent with ecologically driven evolution of immune functions. Recently qPCR analyses showed that expression of mTOR pathway components in skeletal muscle correlates with the SB-charr form in Iceland 54 , but it is unknown whether there is genetic differentiation in those genes or upstream regulators.…”
Section: Introductionsupporting
confidence: 57%
“…The genetic separation in two immunity genes among sympatric morphs in Lake Thingvallavatn 52 prompted us to examine further the expression of Lyz and nattl that were differentially expressed between morphs.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations